Instrumenty polityki mikro- i makroostrożnościowej w sektorze ubezpieczeń - Czerwińska, Teresa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The purpose of this study is to analyze key characteristics of micro- and macroprudentialapproaches to supervision regulations in the insurance sector. Analysisof micro- and macroprudential policy instruments reveal common sources butdifferent aims of the instruments. Macroprudential instruments are used to reducesystematic risks, while microprudential instruments are used to provide liquidityand solvency. Bearing in mind the relatively low potential of the insurance sectorfor risk creation, it seems that macroprudential instruments should be closelyconnected with microprudential instruments. However, it is the microprudentialinstruments that need to play the key role.